If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(9x + -6)(3x + 9) = 0 Reorder the terms: 8(-6 + 9x)(3x + 9) = 0 Reorder the terms: 8(-6 + 9x)(9 + 3x) = 0 Multiply (-6 + 9x) * (9 + 3x) 8(-6(9 + 3x) + 9x * (9 + 3x)) = 0 8((9 * -6 + 3x * -6) + 9x * (9 + 3x)) = 0 8((-54 + -18x) + 9x * (9 + 3x)) = 0 8(-54 + -18x + (9 * 9x + 3x * 9x)) = 0 8(-54 + -18x + (81x + 27x2)) = 0 Combine like terms: -18x + 81x = 63x 8(-54 + 63x + 27x2) = 0 (-54 * 8 + 63x * 8 + 27x2 * 8) = 0 (-432 + 504x + 216x2) = 0 Solving -432 + 504x + 216x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '72'. 72(-6 + 7x + 3x2) = 0 Factor a trinomial. 72((-3 + -1x)(2 + -3x)) = 0 Ignore the factor 72.Subproblem 1
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 2
Set the factor '(2 + -3x)' equal to zero and attempt to solve: Simplifying 2 + -3x = 0 Solving 2 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -3x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + -3x = 0 + -2 -3x = 0 + -2 Combine like terms: 0 + -2 = -2 -3x = -2 Divide each side by '-3'. x = 0.6666666667 Simplifying x = 0.6666666667Solution
x = {-3, 0.6666666667}
| -1.5x^2+8x+10.5=0 | | 3x10^8/6x10^8 | | 80=173-v | | X^2-360x-34=0 | | 9x^2-18x-16= | | -r^2+r=7r+9 | | 46=4x-6(7x+24) | | -v+217=153 | | 20x^2-70x+50= | | 600+25=53.50 | | 2x-y+3y-5x= | | (2cosx)(3sinx)-3=0 | | (3x-2)(3x-8)= | | 53.50/30 | | 36n=35n | | 3/2x-4/5x/1/3-2/x | | 5-2(T+4)=(3T+12) | | X+6=-40 | | Ln(x+12)=8 | | 972=x(3x) | | 7x+8y+(-8y)+(-9x)= | | 1/4=y=12 | | 40x^2+116x+84= | | -8n^2-12n+14=8 | | -x-178=5x+176 | | 700=29*24 | | -27.6=18.1+m | | X^2-17=17 | | 2k^2=49+7k | | -9=-m | | -27.6=18.1m | | -n^2-15n+72=-9n |